Treatment of lung cancer using nanoparticle drug delivery systems - Chandolu, V.; Dass, Crispin (Bentham Science Publishers Ltd., 2013)
Context: One of the leading causes of cancer-associated deaths in most men and women in the Western world is lung cancer. There are various types of treatments depending on the type and the stage of the cancer. A recent type of therapy is targeted gene therapy which aims to target genes that cause lung cancer. However, this therapy has some drawbacks including lack of proper vectors for delivery. These drawbacks can potentially be overcome by using various types of nanoparticles.Objective: To review current literature on the treatment of lung cancer with nanoparticles.Methods: Researchers have attempted to treat lung cancer with a variety of types of nanoparticle matrices including lipid, polylactide-co-glycolide, albumin, poly (-pentadecalactone-co-butylene-co-succinate), cerium oxide, gold, ultra-small superparamagnetic iron oxide nanoparticles, super paramagnetic iron oxide, lipid–polycation–DNA, N-[1-(2,3-dioleoyloxyl)propyl]-NNN-trimethylammoniummethylsulfate, silica-overcoated magnetic cores, and polyethyleneglycol phosphatidylethanolamine. There are various ways in which nanoparticles enhance drug delivery, and these include encapsulation against immune response, tissue penetration, target selectivity and specificity, delivery monitoring, promoting apoptosis, and blocking pathways for cancer initiation and progression.Conclusion: In the past decade, a lot has been said about targeting of NPs for lung and other cancers, but little has been actually successfully delivered to date. Nevertheless, nanoparticles can act as good vectors for delivering drug to the target neoplastic lesions within the lung, increase cellular uptake, increase tissue penetration and help in tracking the drug. In the future, combination therapies may play a key role in the treatment of lung cancer using the existing therapies.